Exploration of Songket Batik: Production Process and Cultural Values at Rumah Batik Tarancak, Solok City - Sari, Macita; Suci, Puji Hujria (LPPM Institut Seni Indonesia Padangpanjang, 2024)
Batik is one of Indonesia’s cultural heritages that holds high artistic value, particularly in its motifs and philosophical meanings. An innovative development in West Sumatra is the creation of batik songket, a fusion of batik art and the traditional Minangkabau songket weaving. This study focuses on the production process of batik songket at Rumah Batik Tarancak in Solok City, a pioneer in producing batik on songket fabrics in the region. This innovation not only enriches local cultural heritage but also supports the local economy by enhancing the quality of products that can compete in the broader market. This research was conducted using a qualitative descriptive method through direct observation, interviews, and documentation at Rumah Batik Tarancak. The findings reveal that the batik songket production process employs traditional manual weaving tools (ATBM) and uses both natural and synthetic dyes. The motifs are inspired by Minangkabau culture, embodying symbolic and aesthetic meanings. This innovation is expected to help preserve the heritage of batik and songket while raising awareness about the importance of maintaining cultural traditions.